Sight or Insight: accounting for the visual in design research - Worden, Suzette (3rd Doctoral Education in Design, Department of Design and Architecture, Chiba University, 1-33 Yayoi-cho, Inage-ku, Chiba-shi, Chiba-ken, 263-8522 Japan, 2003)
There has always been plenty of scope for examining the visual in relation to design practice and design research. In design research, methodologies have often been adapted from other disciplines. This is most evident in academic studies of the consumption of design and representations of design, where skills from visual culture studies or semiotic analysis have become integral to design research and analysis. This paper will consider whether doctoral students in design can continue to adopt, or adapt skills from other disciplines in order to make sense of the visual in design. Or, is the act of creating new methodologies for investigating the visual an essential part of a doctoral student's original contribution to knowledge? As a response to this question, this paper will examine conceptions of the 'visual' and reflexive forms of visual analysis.